Adult first-generation immigrants and cardiovascular risk factors in the Veneto Region, Northeast Italy - Dalla Zuanna, Teresa; Batzella, Erich; Pitter, Gisella; Russo, Francesca; Spadea, Teresa; Canova, Cristina (Frontiers in Public Health, 2023)
Introduction The health condition of immigrants traditionally follows a transition from a low disease occurrence to the epidemiological profile of the deprived groups in the host country. In the Europe, studies examining differences in biochemical and clinical outcomes among immigrants and natives are lacking. We examined differences in cardiovascular risk factors between first-generation immigrants and Italians, and how migration pattern variables could affect health outcomes. Material and methods We included participants between 20 and 69 years recruited from a Health Surveillance Program of the Veneto Region. Blood pressure (BP), total cholesterol (TC) and LDL cholesterol levels were measured. Immigrant status was defined by being born in a high migratory pressure country (HMPC) and subdivided by geographical macro-areas. We used generalized linear regression models to investigate differences between these outcomes among immigrants compared to native-born, adjusting for age, sex, education, BMI, alcohol consumption, smoking status, food consumption, salt consumption in the BP analysis and the laboratory in charge for cholesterol analysis. Within immigrant subjects, the results were stratified by variables of the migration pattern: age at immigration and length of residence in Italy. Results Thirty seven thousand three hundred and eighty subjects were included in the analysis, 8.6% were born in an HMPC. Heterogeneous results were seen by the macro-areas of origin and sex, with male immigrants from CE Europe (β = 8.77 mg/dl) and Asia (β = 6.56 mg/dl) showing higher levels of TC than native-born, while female immigrants from Northern Africa showed lower levels of TC (β = −8.64 mg/dl). BP levels were generally lower among immigrants. Immigrants residing in Italy for more than 20 years had lower levels of TC (β = −2.9 mg/dl) than native-born. In contrast, immigrants who arrived <20 years ago or arrived older than 18 years had higher levels of TC. This trend was confirmed for CE Europeans and was inverted for Northern Africans. Conclusions The large heterogeneity in the results depending on sex and macro-area of origin indicates the need for targeted intervention in each specific immigrant group. The results confirm that acculturation leads to a convergence toward the epidemiological profile of the host population that depends on the starting condition of the immigrant group.